Odpowiedzi

Najlepsza Odpowiedź!
2009-12-20T13:49:54+01:00
Metoda podstawiania:
3x + y = -1
4x + 3y = 2

y = -1 - 3x
4x + 3y = 2

y = -1 - 3x
4x + 3(-1 - 3x) = 2

y = -1 - 3x
4x - 3 - 9x = 2

y = -1 - 3x
-5x = 5

y = -1 - 3x
x = -1

y = -1 + 3 = 2
x = -1


2009-12-20T16:50:28+01:00
Metoda przeciwnych współczynników:

3x+y=-1/*(-3)
4x+3y=2

-9x-3y=3
4x+3y=2
+------------
-5x=5/:(-5)
x=-1

-3+y=-1
x=-1

v=2
x=-1

Metoda podstawiania:
3x+y=-1/-3x
4x+3y=2

y=-1-3x
4x-3-9x=2

y=-1-3x
-5x=5/:(-1)

x=-1
y=-1+3

x=-1
y=2